Neoplasms of the testis in child. - Cepellini, Raúl; Pereyra Bonasso, Jorge; Sbárbaro, Orestes; Chizzola, Manlio; Viola Peluffo, Julio C (Cirugía del Uruguay, 1988)
Pathologíc considerations about child's testis neoplasms are done on the basis of a 18 cases serie. There was a germinal tumors predominance and among them in the vitelina sac group. Evolution was generally good. There were three deaths.